2021
DOI: 10.3847/1538-4357/abf6d3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Desorption of Astrophysically Relevant Ice Mixtures of Acetaldehyde and Acetonitrile from Olivine Dust*

Abstract: Millimeter and centimeter observations are discovering an increasing number of interstellar complex organic molecules (iCOMs) in a large variety of star-forming sites, from the earliest stages of star formation to protoplanetary disks and in comets. In this context it is pivotal to understand how the solid-phase interactions between iCOMs and grain surfaces influence the thermal desorption process and, therefore, the presence of molecular species in the gas phase. In the laboratory, it is possible to simulate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…In Figure , we present TPD curves for mass 46 for 13 CH 3 13 CHO and CH 3 CHO (as a reference curve). The peak at ∼100 K corresponds to the desorption of acetaldehyde . The TPDs are shown up to 200 K as there are misleading peaks above 200 K, because of the desorption of 13 C-bearing formamide ,, and, possibly, H 13 COO – …”
Section: Resultsmentioning
confidence: 99%
“…In Figure , we present TPD curves for mass 46 for 13 CH 3 13 CHO and CH 3 CHO (as a reference curve). The peak at ∼100 K corresponds to the desorption of acetaldehyde . The TPDs are shown up to 200 K as there are misleading peaks above 200 K, because of the desorption of 13 C-bearing formamide ,, and, possibly, H 13 COO – …”
Section: Resultsmentioning
confidence: 99%
“…We will first compare the case of the pure acetaldehyde ice. Here, experiments provide a BE of 4650 K, while calculations dealing with the ideal model of a molecule above the (010) acetaldehyde surface gives a BE of 2650 K. Given the robustness of the measurement (confirmed by Corazzi et al 2021), one would conclude that what is measured does not correspond to what is calculated. In reality, when a molecular film is heated, it will constantly reorganise itself, and the situation of a molecule on top of the surface is not the most energetically stable configuration.…”
Section: Pure Acetaldehyde Icementioning
confidence: 88%
“…Comparison with previous experimental estimates: Now we have a tool to compare BE provided by different values of pre-exponential factors. Corazzi et al (2021) recently reported an experimental value of BE=3100 K of acetaldehyde co-deposited with water on a substrate made of micrometer-sized olivine grains. It obviously differs from the measured values here and it is lesser than any calculated value.…”
Section: The Importance Of the Pre-exponential Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Chaabouni and coworkers (2018) provided desorption energies of methylamine and formamide from amorphous solid water. In recent work, Corazzi et al (2021) studied the sublimation of acetaldehyde and acetonitrile from olivine dust. Each of the different iCOMs presented different desorption profiles, which depend on the desorption substrates.…”
Section: Introductionmentioning
confidence: 99%